2001
DOI: 10.1007/s004280000289
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and kinetic features of transitional cell carcinomas of the bladder: biological and clinical implications

Abstract: Molecular and kinetic analyses have contributed to our understanding of the biology of transitional cell carcinomas (TCC) of the bladder. The concordant pattern of X-chromosome inactivation of multiple TCCs appearing at different times and at different sites and concordant genetic abnormalities in a subset of muscle-invasive TCC strongly support a monoclonal origin and a homogeneous tumor cell selection throughout the neoplasm. However, topographic intratumor heterogeneity results from the accumulation of gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 56 publications
(89 reference statements)
3
29
0
Order By: Relevance
“…With the use of image analysis subtle morphological nuclear abnormalities that are not readily seen by the human eyes have been 4 demonstrated in urinary bladders harboring preneoplastic and neoplastic lesions. Recent studies showed that 50% of the histologically normal urothelium adjacent to superficial urothelial carcinoma has genetic anomalies on chromosome 9, similar to the anomalies found in the coexistent carcinoma [4,5]. In addition, non-diploid histograms occur in 4.2-53.5% of normal-looking urothelium adjacent to bladder tumors (L. Andersson, personal communication).…”
Section: Malignancy-associated Changesmentioning
confidence: 91%
“…With the use of image analysis subtle morphological nuclear abnormalities that are not readily seen by the human eyes have been 4 demonstrated in urinary bladders harboring preneoplastic and neoplastic lesions. Recent studies showed that 50% of the histologically normal urothelium adjacent to superficial urothelial carcinoma has genetic anomalies on chromosome 9, similar to the anomalies found in the coexistent carcinoma [4,5]. In addition, non-diploid histograms occur in 4.2-53.5% of normal-looking urothelium adjacent to bladder tumors (L. Andersson, personal communication).…”
Section: Malignancy-associated Changesmentioning
confidence: 91%
“…Alterations of Rb gene have been observed in several epithelial tumours suggesting that structural abnormalities, including mutations and/or deletions of the Rb gene, may result in the inactivation of tumour suppressor protein and may be involved in tumorigenesis [45]. Although conflicting results of pRb expression in bladder cancer have been shown by some investigators, they found an important prognostic expressing variable [46][47][48]. In the present study we have found no relationship between cyclin D1 overexpression and the loss of Rb protein suggested the non-existence of an Rb-cyclin D1 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 However, the association of multiple genetic alterations would become statistically less probable as the number of molecular markers increases and is useful to test clonal expansions in tumors. 7,18 Although genetic abnormalities are probably asymmetrically acquired, there is a correlation with tumor cell topography in both luminal and solid organs, 1,[19][20][21][22][23] which has not been assessed in skin melanocytic lesions. Any potential topographic segregation of tumor cells will influence interpretations of the results, supporting a linear model if progressive grading is parallel to intraepithelial-to-invasive topography of tumor cells.…”
mentioning
confidence: 99%